The Pursuit of Quality Assurance in Nigerian Universities: Issues and Challenges - Ekpoh, Uduak Imo; Asuquo, Michael Ekpenyong (Mediterranean Journal of Social Sciences, 2020)
The contemporary trend of global competitiveness has brought great concern for provision of quality education. Hence universities are called upon to respond through efforts in ensuring quality assurance in its programmes offerings. This study on the pursuit of quality assurance in Nigerian Universities: Issues and challenges was carried out to sample the perspective of 640 academic staff from four Federal Universities in South-South Nigeria. Survey research design was used for the study. Four research questions guided the study. A 40-item researchersâ€™ developed instrument called â€œQuality Assurance Practices Questionnaire (QAPQ)â€ was used for data collection. The instrument was validated and reliability estimate established through Cronbach Alpha with an index of 0.86. Mean and standard deviation were used to answer the research questions. Findings indicated that various strategies exist to ensure quality assurance. Also the extent of quality assurance implementation is moderate. Findings also showed that many challenges impede the implementation of quality assurance in universities. Suggested remedies by the respondents to improve the implementation of quality assurance include; total commitment of university management to quality assurance, admission of students based on merit, adequate funding and sufficient infrastructural facilities among others.